Pengaruh Hypnopressure terhadap Produksi Air Susu Ibu (ASI) dan Kepercayaan Diri Menyusui - Diah Evawanna Anuhgera; Elsaria Sembiring (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2021)
Breastfeeding is an obligation that must be given to babies during their growth period. Consistent breast milk production and confidence to breastfeed are very necessary for the success of exclusive breastfeeding. Hypnopressure is one method that can increaseand maintain breastmilk production and breastfeeding confidence. The purpose of this project is to analyze the effect of hypnopressure on breast milk production and breastfeeding confidence. This study uses Quasy Eksperimental with Pretest dan Posttest Controlled Group Design. There were 28 postpartum mothers who were divided into two groups and taken with simple random sampling. Production of breast milk was measured by electric breast pump and breastfeeding sel efficacy was measured Breastfeeding Self Efficacy Scale (BSES). Data were analyzed using paired and unpaired t-test. Primary outcomes of this study will be effect of the intervention on breastmilk production and breastfeeding confidence. We conclude that hypnopressure could improve breastmilk production (p=0.00) and breasfeeding confidence (p=0.00) and breastfeeding confidence (p=0.00). Result of this greater understanding about increase breast milk production and confidence which influence the success of breastfeeding by hypnopressure then be useful targets for midwife intervention in post partum.